Equity valuation of Hugo Boss AG - Soares, João Moreira (2021)
This dissertation’s goal is to determine Hugo Boss’s fair share price and then issue a recommendation. The valuation process is based on macroeconomic information, industry outlooks, company business strategy and the company’s historical financial data. To define the share price, two different approaches were used - intrinsic and relative valuation. The methods chosen were the Discounted Cash Flow method (intrinsic valuation) and the multiples method (relative valuation). The share price reached through each method was 49,50€ and 38,35€, respectively. Both values combined allow the conclusion of 43,92€ as the fair value of Hugo Boss’s share price. Comparing the fair price calculated with its current market share price (35,10€) there is a 25% upside potential, which leads to a buy recommendation.